Priest and Layman in a Minority Church: the Roman Catholic Church in the Northern Netherlands 1592–1686 - Spiertz, M. G. (Studies in church history, 1989)
In 1572, when the provinces of Holland and Zeeland were almost completely overrun by the ‘Geuzen’, Pope Gregory XIII (1572-1585) succeeded to the Holy See. In 1578 this Pope forbade the Roman Catholics in the rebellious provinces to give any civil or military service to the rebels’ authority—on penalty of excommunication—and identified Catholicism with being faithful to the Spanish cause. When this Pope died in 1585, there was reasonable hope held in Rome that the recapture of the Northern Netherlands—and hence the restoration of Catholicism—would soon be realized, as Parma’s campaign was succeeding in the South of the Netherlands and one town after another fell into his hands.During the pontificates of Sixtus V (1585-1590) and Clement VIII (1592-1605) it gradually became clear to the Holy See that in the Northern Netherlands an independent state under Calvinist authority might be in the making. In these provinces the episcopal sees, set up in 1559, were either vacant or deserted since the bishops lived in exile. In spite of requests by Philip II the Holy See postponed the appointment of new bishops. However, in 1592 Clement VIII appointed an administrator, a ‘vicar apostolic’, who, in the name of the Pope, was to administer all the provinces where Calvinism had gained the upper hand, notably the area north of the great rivers in the present-day Netherlands. This vicar apostolic Sasbout Vosmeer (1592-1614) was consecrated in 1602 and given the title of archbishop of Philippi inpartibus infidelium.